CHANGING THE LABILE PHOSPHORUS CONTENTS IN THE SOIL USING DIFFERENT FERTILIZATION AND CULTIVATION SYSTEMS - Шевченко, І. М. (Scientific Progress & Innovations, 2013)
It was established on the basis of longstanding field surveys that the usage of mineral and organic fertilizers containing the increased pus portion during crop rotation in the arid submontane – steppe zone leads to the rising of the labile phosphorus contents in the soil. Method of tillage, turnover and mixing factor influence in part the phosphate rate because the allocation of plant rests and fertilizers in the soil depends on them. When using longstanding nonmoldboard tillage the growth rate of phosphorus contents in the soil in the upper layer is less than the rate of drawdown of this element in the lower layer.